Endogenous retroviruses in primates - Brown, Katherine (2015)
Numerous endogenous retroviruses (ERVs) are found in all mammalian genomes and represent retroviruses which have, by chance, integrated into the germline and are transmitted vertically from parents to offspring. In many non-human primates these insertions have not been well-studied. ERVs provide a snapshot of the retroviruses a host has been exposed to during its evolutionary history, including retroviruses which are no longer circulating. Accurate annotation and characterisation of ERV regions is an important step in interpreting the huge amount of genetic information available for increasing numbers of organisms. This project represents an extensive study into the diversity of ERVs in the genomes of primates and related ERVs in rodents, lagomorphs and tree shrews. The focus is on groups of ERVs for which previous analyses are patchy or outdated, particularly in terms of their evolutionary history and possible transmission routes. A pipeline has been developed to comprehensively and rapidly screen genomes for ERVs and phylogenetic analysis has been performed in order to characterise these ERVs. Laboratory study was used to complement the bioinformatics analysis. Almost 200,000 ERV fragments, many of which have not previously been characterised, were identified. A novel endogenous member of the lentivirus genus of retroviruses, which are rarely found in an endogenous form, was identified in the bushbaby Galago moholi. This ERV may represent an ancient ancestor of modern human immunodeficiency virus (HIV). Another retrovirus, gibbon ape leukaemia virus, previously thought to be a common pathogen in gibbons, was found to not exist in contemporary gibbons and a route through which a single cross species transmission event may have resulted in all known cases of this disease worldwide was identified. Endogenous epsilonretroviruses, usually considered to be viruses of fish and amphibians, were identified in all screened species of primates.